1997
DOI: 10.1159/000291838
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Diagnosis of Postabortal Placental Remnant by Sonohysterography and Color Doppler Sonographic Studies

Abstract: The decision whether to perform uterine curettage for postabortal bleeding depends on the ability to demonstrate placental remnants in the uterine cavity. However, diagnosis of postabortal trophoblastic residua by conventional ultrasonography may be inconclusive. We report our experience with the use of combined sonohysterography and color Doppler to demonstrate a placental polyp after early pregnancy termination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
12
1
Order By: Relevance
“…Tal et al 6 also found that the use of color Doppler imaging during sonohysterography significantly increased the diagnostic accuracy in 4 cases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Tal et al 6 also found that the use of color Doppler imaging during sonohysterography significantly increased the diagnostic accuracy in 4 cases.…”
Section: Discussionmentioning
confidence: 95%
“…5 Color Doppler sonographic evaluation of a suspected intrauterine echogenic mass may also help to identify the type of the mass. 5,6 The aim of this prospective cohort study was to evaluate the role of color Doppler imaging during sonohysterography in the diagnosis of residual trophoblastic tissue.…”
mentioning
confidence: 99%
“…10 Combining these methods, color Doppler sonography and sonohysterography, may improve the accuracy of the diagnosis of RPOC over that from conventional sonography. 11 However, the diagnostic value of sonography for the diagnosis of RPOC if performed within 1 week after uterine evacuation is equivocal. Bar-Hava et al 12 emphasized that on sonography the uterine cavity is seldom empty within 1 week after curettage.…”
Section: Discussionmentioning
confidence: 99%
“…Adding color Doppler examination to basic transvaginal 2D ultrasound examination increases detection rate of the retained trophoblastic tissue. [17][18][19] In their recent paper, Alcázar and co-workers 20 suggested that transvaginal color Doppler is a helpful method for detecting retained trophoblastic tissue in patients with first-trimester spontaneous abortion. They analyzed 62 patients with positive urine pregnancy test and history of heavy vaginal bleeding whose gestational age was lass than 14 weeks.…”
Section: Incomplete and Complete Spontaneous Abortionmentioning
confidence: 99%